Toward Evaluating Trustworthiness of Social Networking Site Users: Reputation-Based Method - Algarni, Abdullah; AlMakrami, Hashem; Alarifi, Abdulrahman (Archives of Business Research, 2019)
<span style="font-family: ’Calibri’,sans-serif; font-size: 10.5pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">As social networking sites (SNSs) have risen in popularity, attackers have been using social engineering traps and tactics to trick SNS users into obeying them, accepting threats, and falling victim to various crimes and attacks, such as phishing, sexual abuse, financial abuse, identity theft, impersonation, physical crime, and many other forms. Recent research on SNS security shows that most of the attackers rely mainly on fake identities. However, one of the key challenges that has faced researchers recently is how to distinguish between legitimate users and attackers. In this paper, we propose a simple yet effective method of evaluating the trustworthiness of an SNS user. The proposed method relies on a user’s reputation, which can be evaluated from the user’s friendship history. As such, this method contributes to reducing the risks associated with the lack of identity authentication in SNSs, as well as the failure to filter fake profiles when receiving friendship invitations, looking for people on search engines, and dealing with spam messages.